REINTERPRETATION OF THE GOALS OF ISLAMIC EDUCATION ACCORDING TO PROF. HM ARIFIN - Harahap, Nasrun (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study aims to reinterpret the objectives of Islamic education according to Prof. HM Arifin by situating his ideas within the context of contemporary educational challenges, particularly in integrating the dimensions of faith, knowledge, morality, and social responsibility. The research employs a qualitative library-based method with a conceptual and philosophical approach, using primary data derived from the works of Prof. HM Arifin and secondary data from journal articles, books, and relevant studies on the philosophy and objectives of Islamic education, which are analyzed through content and interpretative analysis. The findings indicate that the objectives of Islamic education according to Prof. HM Arifin is oriented toward the formation of a holistic human being (insān kāmil) through balanced intellectual, spiritual, moral, and social development, so that education is understood not merely as a process of knowledge transfer but also as a means of character formation grounded in divine values while encouraging active human participation in social life. This reinterpretation affirms that Prof. HM Arifin's thought remains relevant in addressing modern educational problems, such as pragmatic tendencies, moral degradation, and the dichotomy between religion and general knowledge, and recommends that future research develop comparative and empirical studies to assess the implementation of these concepts in contemporary educational practice.